Increasingly stable or more stressful? Children and union dissolution across four decades. Evidence from Norway - Elina Vinberg; Rannveig Kaldager Hart; Torkild H. Lyngstad (Statistics Norway, Research Department, 2015)
This study describes the association between having children and the risk of union disruption, and whether this association has changed over time. We expand upon previous research by including data on cohabiting as well as married couples, and by studying change over four decades. We use data from the Norwegian Gender and Generation Study (2007) (N = 14 892). Combining self-reported union histories with register data on fertility histories, we construct a data set of person months for all individuals at risk of union dissolution in the period 1970-2007. Results from the event history analysis confirm that couples with children have lower union dissolution risk. Union dissolution risk is lowest when children are young, and also varies by number of children. There is little change over historical time in the correlation between having children and the risk of union dissolution. However, the monthly risk of dissolving unions increases substantially over time among childless as well as among parental couples.
Keywords: J11; J12; J13; 330; Union dissolution; Fertility; Demographic trends